Legal Protection of the Family: Concept and Manifestations - Djagham, Mohamed; Cherrad, Soufia (Journal of Legal Studies and Researches, 2022)
The family is one of the oldest institutions known to humankind, so it is necessary to scrutinize the conceptual framework of the term family. The idiomatic fog surrounding the term family cast a shadow over the concept of protection, which is numerous and differs between legal systems that always try to take into account the privacy of family ties at the level of criminal, civil or international protection.